Can a structured emulsion (fat in water‐fibre system) substitute saturated fat in cookies without hampering their quality?. (27th August 2021) - Boukid, Fatma; Carini, Eleonora; Curti, Elena; Diantom, Agoura; Corte, Roberto; Vittadini, Elena
Summary: Replacing fat and saturated fat in baked goods without affecting their quality characteristics is a challenging task. This study evaluated complete and partial substitution of saturated fats (butter and palm oil) by structured emulsions [SE, oil (sunflower) – in – water (fibre‐water) emulsion] in cookies by investigating its impact on product quality. Nutritional labelling underlined a drastic reduction in saturated fatty acids [−35% (50% substitution) and −73% (100% substitution)] compared to their conventional counterparts (butter and palm oil). Partial substitution did not markedly affect physicochemical properties, while complete substitution resulted in thinner, harder and darker cookies compared to the controls. Particularly, cookies made with (50:50) structured emulsion – palm oil had the highest sensory scores, and they were perceived as soft, buttery and crunchy. Thus, the use of structured emulsion might be a valuable alternative to develop a potentially healthier product with acceptable sensory properties. Abstract : Structured emulsions for saturated fats substitution in cookies.